2005
DOI: 10.1124/jpet.104.078451
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Changes in Receptor/G-Protein Coupling in Rat Brain following Chronic Monoamine Transporter Blockade

Abstract: The potent tropane analog, WF-23 [2␤-propanoyl-3␤-(2-naphthyl) tropane], blocks dopamine, serotonin, and norepinephrine transporters with high affinity in vitro and blocks transporters for at least 2 days following a single in vivo administration. Previous studies demonstrated desensitization of monoamine receptor-coupled G-proteins in brain following chronic treatment of rats with WF-23. The current study sought to determine the time course of this desensitization and the behavioral effects of receptor desens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…However, it is not known whether these phenomena play a causal role in parkinsonian motor symptoms. Recent evidence in behaving rodents complements earlier data obtained in DA-depleted anesthetized animals and points to a pathological persistence of a post-decision stabilized state of cortical-basal ganglia networks (Mallet et al, 2008;Cruz et al, 2011;Leventhal et al, 2012). However, the parkinsonian symptoms are alleviated by subthalamic nucleus (STN) ablation (Bergman et al, 1990), high-frequency electrical stimulation (Benazzouz et al, 1993;Limousin et al, 1998), and pharmacological inhibition (Levy et al, 2001;Luo et al, 2002), suggesting that STN has a critical role in the symptoms.…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…However, it is not known whether these phenomena play a causal role in parkinsonian motor symptoms. Recent evidence in behaving rodents complements earlier data obtained in DA-depleted anesthetized animals and points to a pathological persistence of a post-decision stabilized state of cortical-basal ganglia networks (Mallet et al, 2008;Cruz et al, 2011;Leventhal et al, 2012). However, the parkinsonian symptoms are alleviated by subthalamic nucleus (STN) ablation (Bergman et al, 1990), high-frequency electrical stimulation (Benazzouz et al, 1993;Limousin et al, 1998), and pharmacological inhibition (Levy et al, 2001;Luo et al, 2002), suggesting that STN has a critical role in the symptoms.…”
Section: Introductionmentioning
confidence: 53%
“…STN, a pivotal nucleus of basal ganglia, exhibits a marked proclivity to sustained burst firing in patients and nonhuman primate and rodent models of the disease (Bergman et al, 1994;Magill et al, 2001;Ni et al, 2001a,b;Galvan and Wichmann, 2008). The mechanism underlying pathological burst activity in STN is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…METH administration (Segal et al, 2005). In addition, O'Connor et al (2005) recently reported that repeated administration of the long-acting DAT inhibitor, WF-23, resulted in a progressive reduction in striatal D2 receptor-stimulated […”
Section: Da-behavior Relationshipsmentioning
confidence: 99%
“…Effects of baclofen treatment on GABA B activation of G-proteins in various regions were determined by [ 35 S]GTPγS autoradiography using baclofen as GABA B agonist (Sim et al, 1996a). We have used similar methods in the past to detect the development of region-selective and time-dependent desensitization of GPCRs following prolonged treatment with their respective agonists (Maher et al, 2001; 2005; Martin et al, 2007; O'Connor et al, 2005; Selley et al, 1997). The pharmacological specificity of baclofen-stimulated [ 35 S]GTPγS binding is confirmed in Figure 1, which shows autoradiograms of baclofen-stimulated [ 35 S]GTPγS binding in rat brain coronal sections assayed in the presence and absence of the GABA B antagonist CGP-54626 (Brugger et al, 1993).…”
Section: Resultsmentioning
confidence: 99%